Synergistic effect of pathophysiological and pharmacological factors on the development of Torsade de Pointes - Milićević, Luka; Nakalamić, Nataša; Davidović, Goran (Halo 194 Scientific Journal of Emergency Medicine, 2026)
Introduction: Torsade de pointes is a polymorphic ventricular arrhythmia linked to delayed ventricular repolarization, presenting with transient dizziness and syncope, and rarely progressing to ventricular fibrillation and sudden cardiac death. Common causes include electrolyte imbalance (hypomagnesemia, hypokalemia), class Ia and III antiarrhythmic drugs, certain antibiotics, bradycardia, and malignancies. Case report: A 74-year-old male was hospitalized at the Clinic of Urology, University Clinical Center Kragujevac, for surgical treatment of bladder cancer. During cardiological evaluation, torsade de pointes ventricular tachycardia was recorded. No structural cardiac abnormalities were found. Comorbidities and contributing factors were identified. Adjustment of pharmacotherapy and correction of electrolyte imbalance led to clinical stabilization. Conclusion: In elderly patients, complex pharmacotherapy requires cautious use of antiarrhythmics due to proarrhythmic risk, with emphasis on regular electrolyte monitoring.